Efecto antimicrobiano in vitro del extracto de hojas de icaco en bacterias mesófilas (Salmonella spp, Escherichia coli, Staphylococcus aureus) - Sabando Loor, Lidia María (2020)
The objective of this research was to evaluate the antimicrobial effect in vitro of icaco plum’s leaf extract against three mesophilic pathogenic bacteria (Salmonella spp, Escherichia coli, Staphylococcus aureus). The extract was obtained from the icaco plum’s leaves using the Soxhlet method with the use of ethanol at 95-99%, subsequently the total of phenols content was quantified using the Folin-Ciocalteu method. The yield of the ethanolic extract obtained was 16.7%. The antimicrobial test was performed using the method of diffusion on paper discs according to Kirby-Bauer, taking as reference the measurement of the diameter of the inhibition zone of positive control and the measurement of the halo of the extract. The paper disc diffusion test showed sensitivity to all the bacteria evaluated, presenting for Escherichia coli a minimum halo of 10,67mm at 0,1μg/mL and a maximum diameter of 20,67mm at 10μg/mL, while for Salmonella a minimum value of 8,67mm at 0,1μg/mL and a maximum of 23,33mm at 10μg/mL, on the other hand for Staphylococcus aureus was obtained at least 8, 67mm at 0.1μg/mL and a maximum value of 26,67 mm at 10μg/mL of dilution. The icaco plum’s leaves extract with a concentration of 10μg/mL had better antimicrobial properties for bacteria Gram-negative Escherichia coli, Salmonella and Gram-positive Staphylococcus aureus.